My favorite brunette [videorecording (DVD)] - Nugent, Elliott, 1896-1980; Hope, Bob, 1903-2003; Lamour, Dorothy, 1914-1996; Lorre, Peter; Chaney, Lon, Jr., 1906-1973 (Digiview Productions, 2004)
A photographer is mistaken for a private investigator by a baroness looking for her missing uncle.